2018
DOI: 10.24198/jkp.v6i2.625
|View full text |Cite
|
Sign up to set email alerts
|

Foot Massage Modification to Reduce Blood Pressure in Pregnant Woman with Preeclampsia

Abstract: The Maternal Mortality Ratio (MMR) in Indonesia remains high, including in West Java province. One of the MMR causes is preeclampsia (24%). Currently, the management of preeclampsia is focused on pharmacological therapy. Preeclampsia is characterized by high blood pressure. Some studies revealed that non-pharmacological therapy was effective in dealing high blood pressure including foot massage. Foot message has benefits both physiologically and psychologically. However limited study applied this massage among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
2
1
0
Order By: Relevance
“…Study results were discussed within the framework of the results of other studies on the effect of foot massage applied to groups of women with insomnia and anxiety. These findings are consistent with other studies in which insomnia and anxiety levels are reduced after classical foot massage intervention 19 , 20 , 21 , 31 , 32 . Classical foot massage was shown to be effective in decreasing insomnia and anxiety levels.…”
Section: Discussionsupporting
confidence: 93%
“…Study results were discussed within the framework of the results of other studies on the effect of foot massage applied to groups of women with insomnia and anxiety. These findings are consistent with other studies in which insomnia and anxiety levels are reduced after classical foot massage intervention 19 , 20 , 21 , 31 , 32 . Classical foot massage was shown to be effective in decreasing insomnia and anxiety levels.…”
Section: Discussionsupporting
confidence: 93%
“…Findings of this study aligned with ELShamy and ELSaftey, [13] who found that 30-minute foot reflexology session twice a week for four weeks can reduce blood pressure and improve quality of life of patients with hypertension at Mansoura university hospitals. Also, our findings agreed with Ermiati et al, [24] who demonstrated that, the foot reflexology for 20 minutes daily for one week can reduce blood pressure in pregnant women with preeclampsia. Additionally, EL-Abd et al, [25] found that, foot reflexology for 30 min for 3 months has a significant decrease on blood pressure and heart rate & improve quality of life in individuals suffering from essential hypertension.…”
Section: Discussionsupporting
confidence: 93%
“…There are two main factors causing stunting: the mother's condition and factors due to the child's condition (Rahayuwati et al, 2019;Ermiati, Setyawati, A & emaliyawati, E, 2018). Maternal factors that cause stunting include malnutrition in pregnant women, lack of maternal health during pregnancy, closely spaced pregnancy, and teenage mothers (Budijanto, 2018).…”
Section: Introductionmentioning
confidence: 99%